Rentabilidade vs. Propriedade e Gestão Familiar: o caso das empresas portuguesas do sector do vinho - Pacheco, Luís Miguel (2018)
The objective of this paper is to empirically examine the relationship between firms’ ownership and control structure and their financial performance. The relation between performance and ownership and control structure in the context of family firms (FF) is a less studied topic. The paper is focused on the Portuguese wine firms due to their increasing importance in the Portuguese economy and in the promotion of the country’s exports and image abroad. It is used an unbalanced panel data of 117 firms for the period from 2011 to 2016 and applied a random effects model. The degree of family involvement shows a U-shaped relationship with performance, meaning that those firms where the family does not hold the majority in the board should be open to receive external managers with greater knowledge and experience and increase their internal competencies in order to enhance performance. However, the same is not true when the family has already a majority position in the board. At the light of the agency and stewardship theories, this paper extends the literature performing an application to a less studied sector and country.